Curettage Treatment on Stage III and IV Periodontitis Patients - Harsas, Nadhia Anindhita; Safira, Dhia; Aldilavita, Hanli; Yukiko, Ingetiarani; Alfarikhi, Mochamad Prabu; Saadi, Muhammad Tsany; Feria, Qonita; Kiranahayu, Rarasih; Muchlisya, Shabrina (Journal of Indonesian Dental Association, 2021)
Introduction: Periodontitis is an inflammatory disease of teeth supporting tissue caused by a group of specific microorganism that causes progressive damage to the periodontal ligament and alveolar bone. Periodontal pocket is one of the most important clinical features of periodontal disease. This case report aims to evaluate the results of curettage in periodontitis cases with different stages and grades. Case reports: This report consists of two cases. The first case is a 41-year-old female patient with a chief complaint of gum bleeding during brushing and tooth mobility. Intraoral examination showed gingival redness and swelling, positive papillary bleeding index (PBI) in all regions, and an OHI-S score of 3.16 (poor). A probing depth of 4-5 mm was present on the upper right canine and the lower left central incisor. Gingival recession of 1 mm was also present on the upper right canine. Radiographic examination showed horizontal bone defect that reached the cervical third of the root on the upper right canine and the middle third of the root on the lower left central incisor. The second case is a 61-year-old female patient with a chief complaint of tooth hypersensitivity and tooth mobility since three years ago. Intraoral examination showed gingival redness and swelling with positive PBI in all regions. Oral Hygiene Index- Simplified (OHI-S) score was 3.6 (poor). A probing depth of 4-5 mm and gingival recession was present on both lower left incisors. Grade 1 tooth mobility was also present on the lower left central incisor. Radiographic examination showed horizontal bone defect reaching the apical third of the root. Curettage was performed for both cases after a thorough scaling and root planing. Conclusion: Curettage as a treatment for patients with chronic periodontitis after 4 weeks shows an improvement of patient’s Oral Hygiene Index - Simplified (OHI-S) score and reduced probing depth.